Gastrointestinal system involvement in systemic lupus erythematosus. (October 2017) - Li, Z; Xu, D; Wang, Z; Wang, Y; Zhang, S; Li, M; Zeng, X
Systemic lupus erythematosus (SLE) is a multisystem disorder which can affect the gastrointestinal (GI) system. Although GI symptoms can manifest in 50% of patients with SLE, these have barely been reviewed due to difficulty in identifying different causes. This study aims to clarify clinical characteristics, diagnosis and treatment of the four major SLE-related GI system complications: protein-losing enteropathy (PLE), intestinal pseudo-obstruction (IPO), hepatic involvement and pancreatitis. It is a systematic review using MEDLINE and EMBASE databases and the major search terms were SLE, PLE, IPO, hepatitis and pancreatitis. A total of 125 articles were chosen for our study. SLE-related PLE was characterized by edema and hypoalbuminemia, with Technetium 99m labeled human albumin scintigraphy ( 99m Tc HAS) and alpha-1-antitrypsin fecal clearance test commonly used as diagnostic test. The most common site of protein leakage was the small intestine and the least common site was the stomach. More than half of SLE-related IPO patients had ureterohydronephrosis, and sometimes they manifested as interstitial cystitis and hepatobiliary dilatation. Lupus hepatitis and SLE accompanied by autoimmune hepatitis (SLE-AIH overlap) shared similar clinical manifestations but had different autoantibodies and histopathological features, and positive anti-ribosome P antibody highly indicated the diagnosis of lupus hepatitis. Lupus pancreatitis was usually accompanied by high SLE activity with a relatively high mortality rate. Early diagnosis and timely intervention were crucial, and administration of corticosteroids and immunosuppressants was effective for most of the patients.